2015
DOI: 10.1007/s00464-015-4303-x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta-analysis of studies comparing primary duct closure and T-tube drainage after laparoscopic common bile duct exploration for choledocholithiasis

Abstract: This comprehensive meta-analysis demonstrates that PDC after LCBDE is feasible and associated with fewer complications than TTD. Based on these results, primary duct closure may be considered as the optimal procedure for dochotomy closure after LCBDE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
77
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 51 publications
(86 reference statements)
12
77
0
1
Order By: Relevance
“…Several comparative studies and meta-analysis have demonstrated that primary closure is at least as effective and safe as T-tube drainage [8, 34, 35], even in emergency operation [36] and elderly patients [37]. Long-term outcome also shown that primary closure after LCBDE had a low incidence of recurrent stones, and no biliary strictures [5].…”
Section: Discussionmentioning
confidence: 99%
“…Several comparative studies and meta-analysis have demonstrated that primary closure is at least as effective and safe as T-tube drainage [8, 34, 35], even in emergency operation [36] and elderly patients [37]. Long-term outcome also shown that primary closure after LCBDE had a low incidence of recurrent stones, and no biliary strictures [5].…”
Section: Discussionmentioning
confidence: 99%
“…These injuries are usually recognized with cholangiography; thus, only the small incision used to insert the cholangiocatheter needs to be repaired. Insertion of a T-tube catheter is rather contraindicated, as extension of the laceration to facilitate T-tube insertion results in worsening of the injury and an increased risk of stricture [66]. We recommend suturing the incision using simple interrupted stitches.…”
Section: Class I Injuriesmentioning
confidence: 99%
“…Laparoscopic choledocholithotomy with primary bile duct closure has been reported to be safe compared with T‐tube insertion . Podda et al demonstrated that primary bile duct closure after laparoscopic choledocholithotomy had fewer complications than T‐tube insertion . Retained stones occurred in 1.3% of 444 patients after primary bile duct closure and in 1.4% of 414 patients after T‐tube insertion .…”
Section: Discussionmentioning
confidence: 99%
“…There are various treatment options for removing BDS. Although the best strategy for removing BDS remains controversial, the options include duodenal endoscopic sphincterotomy (EST), laparoscopic or open choledocholithotomy via the transcystic approach or choledochotomy, and primary closure of the bile duct or T‐tube drainage . The size and location of the BDS, the size of the extrahepatic bile duct, and patients' general health affect the treatment choice.…”
Section: Introductionmentioning
confidence: 99%